C-Reactive Protein Stimulates Nicotinic Acetylcholine Receptors to Control ATP-Mediated Monocytic Inflammasome Activation - Richter, Katrin; Sagawe, Sabrina; Hecker, Andreas; Küllmar, Mira; Askevold, Ingolf; Damm, Jelena; Heldmann, Sarah; Pöhlmann, Michael; Ruhrmann, Sophie; Sander, Michael; Schlüter, Klaus-Dieter; Wilker, Sigrid; et al. (Frontiers in Immunology, 2018)
Blood levels of the acute phase reactant C-reactive protein (CRP) are frequently measured as a clinical marker for inflammation, but the biological functions of CRP are still controversial. CRP is a phosphocholine (PC)-binding pentraxin, mainly produced in the liver in response to elevated levels of interleukin-1β (IL-1β) and of the IL-1β-dependent cytokine IL-6. While both cytokines play important roles in host defense, excessive systemic IL-1β levels can cause life-threatening diseases such as trauma-associated systemic inflammation. We hypothesized that CRP acts as a negative feedback regulator of monocytic IL-1β maturation and secretion. Here, we demonstrate that CRP, in association with PC, efficiently reduces ATP-induced inflammasome activation and IL-1β release from human peripheral blood mononuclear leukocytes and monocytic U937 cells. Effective concentrations are in the range of marginally pathologic CRP levels (IC50 = 4.9 µg/ml). CRP elicits metabotropic functions at nicotinic acetylcholine (ACh) receptors (nAChRs) containing subunits α7, α9, and α10 and suppresses the function of ATP-sensitive P2X7 receptors in monocytic cells. Of note, CRP does not induce ion currents at conventional nAChRs, suggesting that CRP is a potent nicotinic agonist controlling innate immunity without entailing the risk of adverse effects in the nervous system. In a prospective study on multiple trauma patients, IL-1β plasma concentrations negatively correlated with preceding CRP levels, whereas inflammasome-independent cytokines IL-6, IL-18, and TNF-α positively correlated. In conclusion, PC-laden CRP is an unconventional nicotinic agonist that potently inhibits ATP-induced inflammasome activation and might protect against trauma-associated sterile inflammation.